Law and the technologies of the twenty-first century : text and materials / by Roger Brownsword, Morag Goodwin. - Brownsword, Roger; Goodwin, Morag (Law in Context., 2012)
Law and the Technologies of the Twenty-First Century provides a contextual account of the way in which law functions in a broader regulatory environment across different jurisdictions. It identifies and clearly structures the four key challenges that technology poses to regulatory efforts, distinguishing between technology as a regulatory target and tool, and guiding the reader through an emerging field that is subject to rapid change. By extensive use of examples and extracts from the texts and materials that form and shape the scholarly and public debates over technology regulation, it presents complex material in a stimulating and engaging manner. Co-authored by a leading scholar in the field with a scholar new to the area, it combines comprehensive knowledge of the field with a fresh approach. This is essential reading for students of law and technology, risk regulation, policy studies, and science and technology studies.